Anno Dracula 1976-1991 : Johnny Alucard - Newman, Kim (Anno Dracula, 2018)
"Transylvania 1976 and the vampire Kate Reed is on the set of Francis Ford Coppola's troubled production of Dracula. Fallen from grace and driven from the British Empire, the Count himself seems long gone. A relic of the past. But when Kate helps a young vampire outcast begin a new life in America, a fresh monster is born. The boy reinvents himself as Johnny Pop and makes his name selling a dangerously addictive drug that confers vampire powers on its users. As Johnny stalks the streets of Manhattan and Hollywood, sinking his fangs ever deeper into the zeitgeist of 1980s America, it seems the past might not be dead after all..."--Publisher description.